Climatic variability and pluviometric trends in a humid tropical environment at Resende municipality- middle Paraíba do Sul river valley (Rio de Janeiro- Brazil). (Brazilian Geographical Journal, 2011)
The global warming of the planet, motivated by an increase in the concentration of atmospheric CO2, is already a well-accepted trend among research works that analyze the different General Circulation Models (GCM). However, a smaller number of research works have been dedicated to analyzing the influence of this variability in the precipitation trends, and its consequences in the structure and functionality of geo-ecosystems.  The present study aims at analyzing the regimen and the rainfall distribution trends in a city in the state of Rio de Janeiro during the course of the last 60 years.  Daily, monthly, and yearly precipitation data were analyzed in an attempt to identify possible regimen changes based on the temporal comparison of data. Initially the annual precipitation trend line was identified, along with the average regimen of the three driest years, the three rainiest years, and the three intermediary years. After that, we analyzed the distribution regimen for dry days and months, the distribution of precipitation based on five intensity classes, and the inter-annual Precipitation Concentration Index (PCI). Among the results, the highlight is a progressive reduction trend of the total annual precipitation (approximately 8% during the course of the period in question), which reinforces the role of regional circulation in the regulation of the local pluviometric totals.  The results obviously indicate an intensification of the seasonality associated to an increase in the frequency of higher intensity rainfall events, which is accompanied by a reduction in the frequency of lower intensity events, which, in turn, are responsible for the hydrological stability of environmental systems. Therefore, the variation in the rainfall distribution regimen is fundamentally a result of the annual variability of most intense daily rainfall frequency, the consequences of which can refer both to an increase in the generation of natural disasters and in the modification of interspecific  relation in geo-ecosystems.